Developing management effectiveness: The nexus between teaching and coaching. Issue 1 (March 2020) - Reid, Alison; Cook, Jonathan; Viedge, Conrad; Scheepers, Caren Brenda
Abstract: As a contribution to the evolving debate about the future of business schools, we explore the complementary value of teaching and coaching in executive education to offer a more holistic individualised learning experience. Beginning in each case with teaching, some enriching differences are: focus on knowing at a macro-level versus doing at a micro-level; pre-determined context-free knowledge versus self-determined context-specific knowledge; impersonal access to many subject experts versus personal access to one process professional; directively taking people out of themselves versus nondirectively taking people into themselves; critical feedback centred on normative reference points versus supportive feedback centred on personalised, formative reference points. The differences reveal limitations in each approach that the other can address. We propose that the greatest benefit for adult learning and management performance can be found at the nexus of the two approaches, when teachers and coaches integrate the qualities of both approaches. This entails not just appreciating some value in the other, but actually incorporating insights and methods from the other approach into their practice. Highlights: The highlights of the current resubmission is the adherence to the reviewers' comments on specifically the PRME principles and these implications for management education. We ensured the implications for practice were highlighted in the relevant section. The faculty development implications were listed.